2017
DOI: 10.1002/adom.201700159
|View full text |Cite
|
Sign up to set email alerts
|

Single CdS Nanorod for High Responsivity UV–Visible Photodetector

Abstract: light absorption, [3] as well as the unique optoelectronic properties. [4][5][6][7] Therefore, many researchers are devoted to synthesize various of 1D nanostructures with controllable size, morphology, orientation, and crystallinity. Until now, various 1D nonostructures including nanorods (NRs), nanowires, nanotubes, and nanobelts [4,5,8,9] have been synthesized by many approaches such as chemical vapor deposition (CVD), focused ion beam, vapor-liquid-solid and chemical solutions. [10][11][12][13] Among 1D na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…Complementary to gapless materials such as graphene, 2D TMDs have numerous exceptional properties, such as a direct bandgap, strong spin‐orbit coupling, and excellent electronic and optical properties resulting from quantum confinement 1‐13 . This increases the potential for furthering the basic understanding of TMDs and for their use in cutting‐edge applications in electronics, 14‐20 spintronics, 21‐26 optoelectronics, 27‐32 and energy harvesting, 33‐38 among others. The preparation of 2D TMDs determines the purpose of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Complementary to gapless materials such as graphene, 2D TMDs have numerous exceptional properties, such as a direct bandgap, strong spin‐orbit coupling, and excellent electronic and optical properties resulting from quantum confinement 1‐13 . This increases the potential for furthering the basic understanding of TMDs and for their use in cutting‐edge applications in electronics, 14‐20 spintronics, 21‐26 optoelectronics, 27‐32 and energy harvesting, 33‐38 among others. The preparation of 2D TMDs determines the purpose of the material.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MoO 3 nanobelts (NBs) and SnO 2 NBs are the same wide‐bandgap 1D semiconductors, and have been studied in the field of light detection . Among the II‐VI compounds, sulfide semiconductors are also an important part …”
Section: Low‐dimensional Semiconductor Nanomaterialsmentioning
confidence: 99%
“…[108][109][110][111] Among the II-VI compounds, sulfide semiconductors are also an important part. 65,[112][113][114][115] V-VI semiconductor nanowire is another type of 1D material, which is widely used in the field of optoelectronics such as PDs. 68,[116][117][118][119][120][121][122] Photoelectric devices prepared based on Bi 2 S 3 NWs, Sb-Bi-Se NWs, Sb 2 Se 3 NWs, and so on, all exhibited excellent characteristics; for example, the high spectrum responsivity of Sb-Bi-Se NWs 116 and the ultra-fast response time of Bi 2 S 3 NWs.…”
Section: D Materialsmentioning
confidence: 99%
“…[30] Pan et al reported an intensity ratio I 2LO /I 1LO of ≈0.22 for the bulk CdS, [31] while Zhao et al, reported a much higher intensity ratio of 1.97 for 1D CdS nanorods. [23] Also in comblike CdS branched nanostructures, due to the existence of trunk-branch junctions, the intensity ratio of I 2LO /I 1LO at the junctions reaches 1.90, which is higher than that at the trunk and branch parts. [32] Additionally, few layer graphene has a huge amount of free electrons due to the overlapping of the conduction and valence bands.…”
Section: Introductionmentioning
confidence: 99%